2010
DOI: 10.3109/02699050903516872
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between severity of traumatic brain injury (TBI) and extent of auditory dysfunction

Abstract: An association was observed between the extent of auditory dysfunction and severity of TBI. This association was more pronounced for hearing status at high frequencies and ABR/MLR components. ABR Wave V absolute latency and I-V interpeak latency increased with severity of TBI. Amplitude of MLR wave Na and Pa decreased with increasing severity. It is suggested that subjects should be evaluated for hearing difficulties based on their severity of TBI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
39
1
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(43 citation statements)
references
References 14 publications
1
39
1
2
Order By: Relevance
“…Shin et al (1989), Rappaport et al (1991a); Cusumano et al (1992), Guérit et al (1993), Keren et al (1994), Soldner et al (2001), Nölle et al (2004), andFischer et al (2008) did not find ABRs to provide useful prognostic information in assessments of patients with severe TBI. However, Ganes and Lundar (1988), Kane et al (1996), Liesiene et al (2008), andMunjal et al (2010) reported that ABR results did correlate with functional outcomes of TBI patients.…”
Section: Wavementioning
confidence: 90%
See 1 more Smart Citation
“…Shin et al (1989), Rappaport et al (1991a); Cusumano et al (1992), Guérit et al (1993), Keren et al (1994), Soldner et al (2001), Nölle et al (2004), andFischer et al (2008) did not find ABRs to provide useful prognostic information in assessments of patients with severe TBI. However, Ganes and Lundar (1988), Kane et al (1996), Liesiene et al (2008), andMunjal et al (2010) reported that ABR results did correlate with functional outcomes of TBI patients.…”
Section: Wavementioning
confidence: 90%
“…A study by Munjal et al (2010) helps to clarify the relationship between MLRs and severity of TBI. These authors collected data from 290 patients: 150 with mild TBI, 100 with moderate TBI, and 40 with severe TBI.…”
Section: Middle Latency Responses (Mlrs) In Assessments Of Tbi Patientsmentioning
confidence: 99%
“…Such exposure frequently results in blast-induced TBI (Terrio et al, 2009). While the most common symptom associated with TBI is non-headache and headache pain, Service Members with a history of TBI often seek treatment for other symptoms that can include sleep disorders, memory loss, cognitive dysfunction, and hearing problems (Bergemalm and Lyxell, 2009; Farmer et al, 2016; Hoover et al, 2015; Krause et al, 2014; Lew, 2007; Munjal et al, 2010; Oleksiak et al, 2012). These symptoms may resolve within weeks to months after injury (Kwok et al, 2009; Levin et al, 1987); however, in a subset of patients these problems persist and worsen into debilitating post-concussion syndrome (McKee and Robinson, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…die akustisch-mechanische Überstimulation (akustisches Trauma), was in beiden Fällen zu einem Funktionsverlust der Haarsinneszellen führt [18,19,21]. Dafür spricht auch, dass es kontralateral einer laterobasalen Fraktur durch die sich intrazerebral ausbreitende Druckwelle zu einer akuten Ertaubung kommen kann [29].…”
Section: Diskussionunclassified
“…B. Schlag auf den Kopf, Kopfanprall in die Kopfstütze) als hydrodynamische Welle direkt in das Innenohr übertragen werden (und dort entsprechende Schäden an den Zellen und Grenzmembranen anrichten) [6]. Andererseits treten an den Sinneszellen auch direkte mikromechanische Schäden durch Abrisse und Einblutungen nach solchen Unfallmechanismen auf [18,19]. Beide Pathomechanismen verursachen überwie-gend temporäre Hörstörungen, sodass (jenseits der oben beschriebenen Frakturen mit sofortiger Ertaubung) die Prognose tendenziell gut ist, wenn eine sofortige Behandlung eingeleitet wird [5].…”
unclassified